Estudo comparativo entre soluções para edifícios de alvenaria estrutural em função do número de paredes estruturais e o tipo de laje - Lavandoscki, Fabio Ioveni (Universidade Federal de São Carlos, 2010)
Structural masonry buildings are being increasingly employed in construction. Well established for low-income buildings and with small insterspace, the system of structural walls has been gaining elbow room on the civil building industry. The great use of this structured system is due to the fact that the building companies, looking for cost reductions has generated great amout of comparative studies among several constructive systems. Recently the structural walls system is being used also in mid and high level buildings which has as main characteristics, bigger flooring number and layout flexibility. However this characteristics can compromise the structured behavior of the buildings and still increase the production costs. This work presents a comparative analysis among 4 floor buildings under this perspective. Three conceptual blueprints are proposed, on which distinct structural solutions, changing the ratio between the amount of structural and sealing walls are considered: with 100%, 90%, 80% and 75% of structural walls. For these situations, different types of slab solutions are considered: one-way joist slab and flat slab. For each solution the amount of materials calculated and the structural behavior is analyzed, aiming to establish parameters that can represent the influence of the number of structural walls over these factors.
Comparative among solutions for structural masonry in function of a number of structural walls and types of slab
Keywords: Construção civil; Edifícios; Custos; Projeto estrutural; Lajes; Structural masonry; Slabs; Structural analysis; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL